Optimal Management of GDP Components - OLIINYK, Viktor (Journal of Advanced Research in Law and Economics, 2018)
The article considers the problem of the management of GDP for different countries. Trade balance is one of the components GDP and it performs as management function. The problem is solved by means of Pontryagin maximum principle. The condition of optimality represents the minimization of discounted consumer spending. Optimal trajectories of GDP of some countries from the specified initial position (2016 year) until specified final state (2021 year) are shown.